Refactoring of UML models using AGG - Folli, Alessandro; Mens, Tom (Electronic Communications of the EASST, 2008)
Model refactoring is an emerging research topic that is heavily inspired by refactoring of object-oriented programs. Current-day UML modeling environments provide poor support for evolving UML models and applying refactoring techniques at model level. As UML models are intrinsically graph-based in nature we propose to use graph transformations to specify and apply model refactoring. More in particular, we use a specific graph transformation tool, AGG, and provide recommendations of how AGG may be improved to better support model refactoring. These recommendations are based on a small experiment that we have carried out with refactoring of UML class diagrams and state machines.